Hubungan DPR dan BPK dalam Melaksanakan Fungsi Pengawasan - AD Basniwati (Jatiswara, 2015)
The existence of the House of Representatives (DPR) to the Supreme Audit Agency (BPK) is an implementation of a power-sharing horizontally in order to perform the functions of state institutions in the capacity and parallel position. Parliament is an institution that state institutions have a legislative function, the function of the budget, and monitoring functions. While the Audit Board is an institution with a state institution whose primary function as a body of state financial check on the tasks of the state. In performing supervisory functions there are two state agencies that have oversight function in this field, namely the House of Representatives and the CPC, in this case the House of Representatives to supervise in politics while the CPC conduct supervision in the financial sector. The results of the financial audit conducted by the CPC in return it back to Parliament to be discussed, so that in carrying out the functions of a connection between the two.